2012
DOI: 10.2337/db12-0049
|View full text |Cite
|
Sign up to set email alerts
|

Rapamycin/IL-2 Combination Therapy in Patients With Type 1 Diabetes Augments Tregs yet Transiently Impairs β-Cell Function

Abstract: Rapamycin/interleukin-2 (IL-2) combination treatment of NOD mice effectively treats autoimmune diabetes. We performed a phase 1 clinical trial to test the safety and immunologic effects of rapamycin/IL-2 combination therapy in type 1 diabetic (T1D) patients. Nine T1D subjects were treated with 2–4 mg/day rapamycin orally for 3 months and 4.5 × 10 6 IU IL-2 s.c. three times per week for 1 month. β-Cell function was monitored by measuring C-peptide. Immunologic changes were monitored u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
247
1
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 286 publications
(256 citation statements)
references
References 43 publications
7
247
1
1
Order By: Relevance
“…Downstream of the cytokine receptors, small molecule inhibitors of JAKs have proven to be successful as potent immunosuppressants, but their ability to target specific T helper cell activities is limited because several cytokine receptors use each kinase 34 . Blockade of mTOR activity with rapamycin in type 1 diabetes is already under investigation in combination with IL-2 to promote T Reg cell function 177 . However, enhanced T Reg cell frequencies with rapamycin and IL-2 is transient because, as discussed, it seems that inhibition further up the signalling cascade at AKT is most important for the promotion of T Reg cell stability and function 79,80 .…”
Section: Bet Inhibitorsmentioning
confidence: 99%
“…Downstream of the cytokine receptors, small molecule inhibitors of JAKs have proven to be successful as potent immunosuppressants, but their ability to target specific T helper cell activities is limited because several cytokine receptors use each kinase 34 . Blockade of mTOR activity with rapamycin in type 1 diabetes is already under investigation in combination with IL-2 to promote T Reg cell function 177 . However, enhanced T Reg cell frequencies with rapamycin and IL-2 is transient because, as discussed, it seems that inhibition further up the signalling cascade at AKT is most important for the promotion of T Reg cell stability and function 79,80 .…”
Section: Bet Inhibitorsmentioning
confidence: 99%
“…Individuals carrying the rs12722495 susceptibility gene, which encodes an IL-2RA haplotype, exhibit reduced proliferative responses to IL-2 and decreased suppressive function of Tregs in vitro, which presumably indicates impaired Treg function in these patients [40,41]. Notably, in response to IL-2, this defect appears to be reversible: in a previously conducted clinical trial of exogenous IL-2, the impaired STAT5 phosphorylation was improved [39,42].…”
Section: Treg Overview and Role In Dmmentioning
confidence: 99%
“…This transcription factor is essential for Treg expansion and survival. A prior clinical trial with IL-2 and rapamycin showed that this signaling pathway improved in the Tregs from the T1D patients at least one year post treatment [42]. We addressed whether the in vitro-expanded Tregs would have similar improvement following culture with exogenous IL-2.…”
Section: Treg Manufacture For Clinical Usementioning
confidence: 99%
See 1 more Smart Citation
“…146 Although this combination therapy increased Treg numbers in the first month, it also transiently impaired β-cell function.…”
Section: Disclosure Of Potential Conflicts Of Interestmentioning
confidence: 99%